Regulating Capital Flows at Both Ends : Does it Work? - Ghosh, Atish (IMF Working Papers; Working Paper, 2014)
This paper examines whether cross-border capital flows can be regulated by imposing capital account restrictions (CARs) in both source and recipient countries, as was originally advocated by John Maynard Keynes and Harry Dexter White. To this end, we use data on bilateral cross-border bank flows from 31 source to 76 recipient (advanced and emerging market) countries over 1995-2012, and combine this information with a new and comprehensive dataset on various outflow and inflow related capital controls and prudential measures in these countries. Our findings suggest that CARs at either end can significantly influence the volume of cross-border bank flows, with restrictions at both ends associated with a larger reduction in flows. We also find evidence of cross-border spillovers whereby inflow restrictions imposed by countries are associated with larger flows to other countries. These findings suggest a useful scope for policy coordination between source and recipient countries, as well as among recipient countries, to better manage potentially disruptive flows.